Western Transitology and Chinese Reality: Some Preliminary Thoughts - Kjeld Erik Brødsgaard (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2011)
It is the object of considerable debate in Western scholarship whether an authoritarian political order dominated by a strong communist party can continue to exist in China given the many challenges stemming from internal reform and the impact of globalization. Will China eventually turn democratic and will the communist party become obsolete and disappear, just as has happened in many other former communist countries. There seems to be a general consensus that Chinese political system is bound to change, but there is no agreement as to the direction and form of change...
hdl:10398/8368
Keywords: 330; Politischer Wandel; Systemtransformation; China